INSTRUMENTS OF STATE SUPPORT OF SMALL AND MEDIUM-SIZED BUSINESSES IN UKRAINE UNDER THE CONDITIONS OF MARITAL STATE - Сімків, Ліля Євгенівна; Чорний, Петро Петрович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2024)
The article examines the instruments of state support for small and medium-sized businesses in Ukraine under martial law. The negative consequences for domestic business caused by military aggression are analyzed. It was established that the partial or complete stoppage of the activities of some enterprises due to active hostilities, complications of logistics, loss of sales markets, a significant change in the structure of demand and production, a decrease in the solvency of the population, and the lack of a sufficient number of qualified employees negatively affected the work of small and medium-sized businesses. It is well-founded that state support for small and medium-sized businesses should become a real catalyst for change and a key factor for the recovery of the country’s economy. As a result of the study, it was established that the state program "Affordable loans 5-7-9%" helps to stimulate and restore business and has shown its effectiveness and efficiency in supporting business during wartime. It was established that the governmental relocation program of enterprises was an effective measure in the system of state support for small and medium-sized businesses, which created favorable conditions for the preservation of human resources, economic potential, and the activation of industrial and entrepreneurial activities. The main advantages and risks faced by the owners of the relocated business are highlighted. Another effective tool of state support for business is the new grant program from the Government isRobota, which is aimed at creating one’s own business, developing small and medium-sized enterprises, as well as for obtaining education. It has been proven that an important step in overcoming the problems of business development in Ukraine under the conditions of martial law on the part of the state is the support of exports and the search for new markets, which will help reduce dependence on the domestic market. It was determined that the creation of stable conditions for the development and functioning of small and medium-sized businesses in Ukraine today requires a comprehensive approach, which should include measures to reduce corruption, improve the legal system, reduce bureaucratic burdens and provide protection of property rights.